The Moderating Roles of Environmental Awareness and Product Knowledge on the Impact of Marketing Mix Elements on Purchase Intention - Tripopsakul, Suchart (International Review of Management and Marketing, 2024)
The purpose of this study is to examine the moderating effects of environmental awareness (EA) and product knowledge (PK) on the relationship between marketing mix elements and the purchase intention of electric vehicles (EVs) in Thailand. Based on a quantitative research design, 253 samples of Thai respondents aged 20 and above were collected via an online questionnaire as a research tool. Structural Equation Modeling (SEM) analysis was used to analyze the proposed hypotheses. The results indicate that all four marketing mix elements, which are product attributes, pricing strategy, distribution channels (place), and promotional activities, significantly influence the purchase intention of electric vehicles. Product attributes (b = 0.523) have the strongest impact on purchase intention, followed by pricing strategy (b = 0.501), distribution channels (place) (b = 0.477), and promotional activities (b = 0.334) respectively. The results of moderation analysis reveal that environmental awareness significantly moderates the effect of product attributes (b = 0.412) and pricing strategy (b = 0.305) on purchase intention but is not found in the relationships of distribution channels (place) and promotional activities toward purchase intention. Additionally, consumer product knowledge of EVs was found to significantly and negatively moderate only the influence of promotional activities (b = -0.343) on purchase intention. In other words, potential consumers who possess higher EV knowledge seem to be less influenced by promotional activities in their decision to buy EVs. These findings highlight the importance of integrating environmental concerns and EV product knowledge into the firm’s marketing strategies to boost EV adoption in emerging countries. The implications and recommendations will be discussed in the paper.